Mesenchymal stromal cells induced regulatory B cells are enriched in extracellular matrix genes and IL-10 independent modulators - Garcia, Sergio G.; Sandoval-Hellín, Noelia; Clos-Sansalvador, Marta; Carreras-Planella, Laura; Morón-Font, Miriam; Guerrero, Dolores; Borràs, Francesc E.; Franquesa, Marcella (Frontiers in Immunology, 2022)
Regulatory B cells (Breg) are essential players in tolerance and immune homeostasis. However, lack of specific Breg markers limit their potential in clinical settings. Mesenchymal stromal cells (MSC) modulate B cell responses and are described to induce Breg in vitro. The aim of this work was to characterize MSC induced Breg (iBreg) and identify specific Breg biomarkers by RNAseq. After 7-day coculture with adipose tissue-derived MSC, B cells were enriched in transitional B cell populations, with increased expression and secretion of IL-10 and no TNFα. In addition, iBreg showed potential to modulate T cell proliferation at 2 to 1 cell ratios and their phenotype remained stable for 72h. RNAseq analysis of sorted IL-10 positive and negative iBreg populations identified over 1500 differentially expressed genes (DEG) among both populations. Analysis of biological processes of DEG highlighted an enrichment of immune regulation and extracellular matrix genes in IL-10- iBreg populations, while IL-10+ iBreg DEG were mostly associated with cell activation. This was supported by T cells modulation assays performed in the presence of anti-IL-10 neutralizing antibodies showing the non-essential role of IL-10 in the immunomodulatory capacity of iBregs on T cells. However, based on RNAseq results we explored the role of TGF-β and found out that it plays a major role on iBreg induction and iBreg immunomodulatory properties. Therefore, we report that MSC induce B cell populations characterized by the generation of extracellular matrix and immune modulation independently of IL-10.